Analysis of smallholder pig value chains in Ghana. Issue 8 (16th November 2020) - Clottey, Joseph K.; Kuwornu, John K. M.; Egyir, Irene S.
ABSTRACT: This article examines the pig value chain in the Kassena Nankana East District of Ghana using data from 108 pig value chain actors. The empirical results revealed that the pig value chain actors added a considerable amount of value, of which processors added the highest value. Processors were perceived to be the most important actors in the governance of the value chain with respect to profit and bargaining power, whereas the producers governed the value chain in terms of information concentration and protection from competition. The results have key policy implications for the production and marketing of pigs in Ghana.